0154 Sleep Inertia Negatively and Consistently Affects Cognitive Speed and Working Memory during Sleep Restriction and Circadian Misalignment. (12th April 2019) - Schreiber, Austin J; Sprecher, Kate E; Burke, Tina M; Ritchie, Hannah K; Wright, Kenneth P
Abstract: Introduction: Sleep inertia is influenced by sleep deprivation and circadian phase. The consistency of individual differences in performance upon awakening from sleep during combined sleep restriction and circadian misalignment has not been investigated. Methods: Twenty adults (8 female) aged 25.6±4.2 years (mean±SD) repeated an 18-day protocol, separated by three days of ad libitum sleep at home. Participants kept habitual, self-selected 8h sleep schedules for two weeks, then stayed in the laboratory for four days. Laboratory visits included one sleep opportunity each day: 8h night one (S1), 3h night two (S2), 3h mornings three (S3) and four (S4). Sleep in the 10 and 30 minutes prior to scheduled waketime were determined by polysomnography. Cognitive function was assessed ~1, 16, and 31 minutes after scheduled waketime after S3 and S4. Cognitive speed and working memory were tested with a 2-minute addition task (number attempted; number correct). Sleepiness was tested using the Karolinska Sleepiness Scale (KSS). Stability of individual differences in cognitive function were quantified by intra-class correlation coefficients (ICC) derived from mixed-model ANOVAs. Results: Average amount of wake in the last 10 and 30 minutes of sleep opportunities was 0.4±0.07 and 1.5±0.20 minutes (mean±SE), respectively. Cognitive speed and working memory were significantly impaired upon awakening and improved thereafter ( p < .05; main effect of time since awakening). There was an interaction between time since awakening and sleep opportunity for the KSS, such that sleepiness scores were similar upon awakening from S3 and S4, but decreased over time to a greater extent after S3 versus S4 ( p < .001). Within an individual, performance was highly consistent (ICC = 0.71-0.90), whereas sleepiness scores were more variable (ICC = 0.28-0.67). Conclusion: Consistent performance upon awakening from sleep during combined sleep restriction and circadian misalignment has implications for development of targeted countermeasures for workers performing safety-critical tasks under sleep inertia (e.g., military, health care and emergency workers). Support (If Any): Office of Naval Research MURI N00014-15-1-2809; NIH TR001082; Undergraduate Research Opportunities Grant, University of Colorado Boulder.